E-Learning As Information Technology-Based Learning Media For Students - I D Sumitra; W Karwati; D A Mariam; D E S Simangunsong (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study was to determine the effectiveness of the Learning Management System (LMS) as an information technology-based learning medium for students of the Indonesian Computer University. This research method uses descriptive quantitative methods. Data collection was carried out by distributing questionnaires using Google Form media and disseminating them via WhatsApp. The scope of the distribution of the questionnaire was limited to 34 respondents with the characteristics of semester 3 to semester 7 students. The results showed that the effectiveness of LMS as an information technology-based learning medium for Indonesian Computer University students was already effective. However, some students argue that face-to-face learning systems are more effective than using LMS. The results of this study conclude that LMS e-learning is effectively used as an Information Technology-based learning medium for students of the Indonesian Computer University. Learning can be said to be effective if the four indicators of learning effectiveness are effective. LMS effectiveness indicators consist of quality, facilities, student readiness to use, and readiness to receive and understand course material.